Integration of fuzzy SERVQUAL and TRIZ models in service quality method - Windi Auliana; Agus Mansur; Muhamad Imron Zamzani; Haswika Haswika; Siti Balkis Mohamed Ibrahim (Universitas Serang Raya, 2026)
Quality service in the field of Occupational Safety and Health (OSH) training is an important factor in supporting effective learning and participant success in the certification process. This study evaluates the quality of OSH training services and proposes solutions to enhance participant satisfaction using PT FTI as a case study. Fuzzy SERVQUAL and TRIZ methodologies were combined to identify inconsistencies between participants’ expectations and perceptions across five dimensions of service quality: physical form, reliability, responsiveness, assurance, and empathy. The results showed three attributes with the highest negative gaps: lack of even-handed attention, unclear information delivery, and perceived irrelevance of training materials. Based on TRIZ principles, the study proposes innovative solutions, such as hybrid training (online and offline), increased information transparency, separation of knowledge and skills evaluation, and rearranging materials to make them more contextual. The combined use of fuzzy SERVQUAL and TRIZ offers a systematic and effective strategy for analyzing and improving training quality.